Studying the long-term adaptation of Haloferax volcanii to low salt conditions: transcriptomic and genetic analyses - Borst, Andreas; Soppa, Jörg (Frontiers in Microbiology, 2026)
Haloferax volcanii is a moderately halophilic archaeon with an optimal salt concentration of 2.1 M NaCl. It is an archaeal model species used for the characterization of various biological processes. It can grow in media with widely varying salt concentrations, but the mechanisms for the adaptation to the extremes of low and high salt are unknown. To get an overview of the adaptation to low salt, the transcriptomes of cultures grown at 0.9 M NaCl were compared to that of cultures grown at the optimal salt concentration of 2.1 M NaCl. Nearly 20% of the transcriptome was found to be differentially regulated. Twelve genes or gene cluster that were induced at low salt were chosen and in frame deletion mutants were generated. Phenotypic analyses revealed that the absence of four proteins led to a growth defect at low salt or totally inhibited growth. Homologous overproduction of three proteins revealed that high levels of HVO_1863 might be lethal, while the production of HVO_B0276 and HVO_0772 in the cognate deletion mutant rescued the phenotype. Taken together, the lower NaCl concentration limit for growth has been established, an overview of differentially regulated genes is presented, and the relative importance of 12 genes has been characterized. For the first time proteins were identified that are very important or essential for growth at low salt, while they are dispensible for growth at the optimal salt concentration.